Korelasi Ilmu Pengetahuan, Metode Ilmiah Dan Penelitian - Utami, Rizki Amalia; Hamdani, Umar; Winarno, Agung (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
Science and the scientific method are two closely related concepts that support the development of research. The scientific method provides a systematic framework for acquiring, validating, and organizing knowledge, while science serves as the theoretical foundation for further exploration. This study employs a Systematic Literature Review (SLR) approach to evaluate the relationship between science and the scientific method in advancing research. By analyzing recent literature, this article identifies patterns, challenges, and opportunities in the application of the scientific method across various disciplines. The findings reveal that the scientific method not only acts as a tool for validation but also as a mechanism for fostering innovation in multidisciplinary research. This highlights its critical role in ensuring the reliability and relevance of scientific advancements.